Determination of hepatitis B genotypes in patients with chronic hepatitis B virus infection in Turkey - (:unkn) unknown (My University, 2005)
BACKGROUND/AIMS: There are significant variations in the geographic distribution of hepatitis B virus genotypes throughout the world, and some genotypes are associated with different clinical outcomes. Eight genotypes of human hepatitis B virus (designated A-H) have been described to date. To determine the hepatitis B virus genotypes in Turkish patients with chronic liver disease and compare the results with clinical characteristics of the patients. METHODS: Fifty-four (pediatric: n=25 and adult: n=29) patients with chronic hepatitis B virus infection and with an hepatitis B virus DNA level above 5 pg/ml were entered into the trial. Restriction fragment length polymorphism method was used to determine hepatitis B virus genotype and their restriction fragment length polymorphism patterns. Hepatitis B virus DNA samples of 13 patients were sequenced automatically for further confirmation of restriction fragment length polymorphism results. RESULTS: Genotype D was the dominant genotype in all of our cases. Among six restriction fragment length polymorphism patterns of genotype D reported in the literature, three (D1, D2, D6) were present in our series and D2 was the most frequent restriction fragment length polymorphism pattern (81.5%). No significant differences were observed among different genotype D restriction fragment length polymorphism patterns with respect to patients' serum ALT, AST, and hepatitis B virus DNA titer, but D2 restriction fragment length polymorphism pattern was significantly more common in younger adults compared to D1 restriction fragment length polymorphism pattern. CONCLUSION: Genotype D with D2 restriction fragment length polymorphism pattern is the dominant hepatitis B virus genotype in all age groups in Turkey.
Keywords: Adult; Female; Humans; Middle Aged; Aged; Turkey; Prevalence; Adolescent; Male; Child; Child, Preschool; Age Distribution; Sex Distribution; Genotype; Polymerase Chain Reaction; Hepatitis B, Chronic; Alanine Transaminase; Aspartate Aminotransferases; Polymorphism, Restriction Fragment Length; Hepatitis B virus; DNA, Viral; Genome, Viral; Hepatitis B Surface Antigens